Single Component Multiphase Lattice Boltzmann Method for Taylor/Bretherton Bubble Train Flow Simulations (Communications in Computational Physics, 2018)
In this study long bubble rising in a narrow channel was investigated usingmultiphase lattice Boltzmann method. The problem is known as a Bretherton or Taylorbubble flow [2] and is used here to verify the performance of the scheme proposedby [13]. The scheme is modified by incorporation of multiple relaxation time (MRT)collision scheme according to the original suggestion of the author. The purpose is toimprove the stability of the method. The numerical simulation results show a goodagreement with analytic solution provided by [2]. Moreover, the convergence studydemonstrates that the method achieves more than the first order of convergence. Thepaper also investigates the influence of simulation parameters on the interface resolutionand shape.